Corporate Criminal Liabilty in Money Laundering Offenses from Online Gambling: A Case Study of PT AJP in the Digital Era - Manullang, Eka Binaria; Br Tarigan, Nopita Sari; Roshinta, Roshinta; Febriyani, Emiliya (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
Digital transformation has significantly reshaped the landscape of economic crime, particularly in the context of money laundering offenses (TPPU) involving or facilitated by corporations. This study examines Indonesia’s positive legal framework governing corporate criminal liability in cases of money laundering, with a specific focus on proceeds derived from online gambling activities. The analysis is grounded in a case study of PT AJP, a corporation designated as a suspect by the Indonesian National Police (Bareskrim Polri) for allegedly receiving and managing funds totalling IDR 40.56 billion originating from online gambling operations. These funds were subsequently utilized for the construction and operation of Hotel Aruss. The corporation's conduct is deemed to fulfil the elements stipulated in Articles 3, 4, and 5 of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering, particularly regarding concealing, disguising, and utilizing criminal proceeds. This article also explores the application of the principles of strict liability and corporate criminal liability, under which a corporation may be held criminally liable irrespective of subjective fault, provided the act is committed by an authorized individual acting on behalf of the corporation. The findings highlight the urgent need for robust and adaptive legal enforcement in addressing technology-driven economic crimes and underscore the importance of regulatory reforms that can effectively respond to the increasingly sophisticated methods employed by corporate actors in the digital era.